Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow